The Influence of Noise Intensity and Age to the Employees’ Blood Pressure at Heavy-Duty Shop and EHS Department - Achmad Fachrul Megananda; Tjipto Suwandi (Universitas Airlangga, 2019)
Introduction: Noise is an unwanted sound heard by the hearers, which can trigger health problems if it continues to be exposed to a certain intensity. One of the health problems that can arise due to noise is the blood pressure increase. This study aims to analyze the influence of noise intensity and age to the blood pressure increase. Methods: This study was an observational study completed with cross-sectional design and analytics. The independent variables in this study were the noise intensity and age, while the dependent variable was the blood pressure. The sample collection of this study applied the total sampling method with 46 employees as respondents, i.e., 29 employees of the heavy-duty shop and 17 employees of the EHS Department in PT. Vale Indonesia. The data analysis was conducted by using the logistic regression statistical test with α-value of 0.05. Results: the noise intensity affected the increase of both systolic blood pressure (significance/p-value=0.00) and diastolic blood pressure (significance/p-value=0.01) with an odds ratio of the increase of systolic blood pressure (Exp (B) =9.75) and the increase of diastolic blood pressure (Exp (B)=5.76). Furthermore, the variable of age does not influence the increase of both systolic (significance/p-value=0.57) and diastolic (significance/p-value=0.41) blood pressures. Conclusion: the rise of the blood pressure of the employees is affected by the noise intensity factor in the workplace. Keywords: noise intensity, age, blood pressure